Unbundling technology adoption and tfp at the firm level: Do intangibles matter? - Michele Battisti; Filippo Belloc; Massimo Del Gatto (Fondazione Eni Enrico Mattei (FEEM), 2012)
We use a panel of European firms to investigate the relationship between intangible assets and productivity. We disentangle between tfp and technology adoption, while available studies so far have considered only a notion of productivity conflating the two effects. To this aim, we estimate production function parameters allowing, within each sector, for the existence of multiple technologies. We find that intangible assets both push the firm towards better technologies (technology adoption effects) and allow for a more efficient exploitation of a given technology (tfp effects).
Keywords: C29; D24; F12; O32; 330; TFP; Intangible Assets; Heterogeneity; Firm Selection; Technology Adoption; Mixture Models; Immaterielles Anlagevermögen; Produktivität; Technologiewahl; Innovation; Betriebswirtschaftliche Produktionsfunktion